INKLUSIFITAS DAKWAH AKUN @NUGARISLUCU DI MEDIA SOSIAL - Hidayatullah, Ahmad (Islamic Communication Journal, 2019)
The rapid development of technology implies inclusiveness in da'wah not only in real terms in the real world, but also in the virtual world. Some things that become considerations of the da'wah inclusiveness need to be applied, including the growth of radicalism through social media, then in 2015 a funny social media account @NUgaris emerged that intensely and consistently helped to color the virtual world. This type of research is qualitative with a case study approach. The authors explore the implementation of preaching inclusiveness through social media carried out by the above account. The results of the study show that there are three forms of the application of the inclusiveness of the @NUgarislucu account, namely: inclusiveness in doing da?wah to the internal citizens of NU (Nahdhiyin); inclusiveness in da'wah to internal Muslims who differ in manhaj (across mass organizations) in Indonesia; inclusiveness in da'wah to external Muslims, namely to other religions in Indonesia. The three forms of missionary inclusiveness are carried out through dialogue and humor.